Records of Aedes (Stegomyia) cretinus in Greece before and after the invasion of Aedes (Stegomyia) albopictus (Diptera: Culicidae) - Athanasios GIATROPOULOS; Georgios BALATSOS; Ioanna LYTRA; Vasileios KARRAS; George KOLIOPOULOS; Dimitrios PAPACHRISTOS; Antonios MICHAELAKIS (European Journal of Entomology)
This manuscript compiles all the available information on the presence of the native mosquito species Aedes cretinus in Greece, before and after the invasion of Aedes albopictus. Mosquito survey data particularly from the Region of Attica, as well as other areas in Greece indicate Ae. cretinus has become scarce since the invasion of Ae. albopictus, which is now widespread. This mini review on Ae. cretinus occurrence in Greece over the years indicates a marked decline in its populations that seems to be related to the prevalence of the invasive mosquito Ae. albopictus, and a need for more comprehensive entomological surveys in areas where these species co-occur.